Dynamic vulnerability of smallholder agricultural systems in the face of climate change for Ethiopia. (11th March 2021) - Shukla, Roopam; Gleixner, Stephanie; Yalew, Amsalu Woldie; Schauberger, Bernhard; Sietz, Diana; Gornott, Christoph
Abstract: Assessing vulnerability to climate change and extremes is the first step towards guiding climate change adaptation. It provides the basis to decide 'what' adaptation measures are needed 'where'. Vulnerability which is defined as a function of exposure, sensitivity, and adaptive capacity, differs spatially and evolves temporally. Therefore, it is imperative to understand the dynamics of vulnerability at sub-national scales to be prepared for and respond to current and future climatic risks. This paper focuses on Ethiopia where a sub-national understanding of vulnerability dynamics in smallholder agriculture systems is missing to date. The paper assesses the vulnerability of crop-based smallholder systems in Ethiopia for the past (1996–2005), current (2006–2015), and two future (2036–2045 and 2066–2075) climate scenarios using an indicator-based approach. The future scenarios are based on two Representative Concentration Pathways (RCPs) RCP 2.6 and RCP 6.0 from four general circulation models. Results show the emergence of highly vulnerable zones that were missing in the past scenario. With Paris agreement pathway, keeping global warming under 2 °C (RCP 2.6), reduction in vulnerability of 10% of the zones is noted in far future (2066–75) as compared to RCP 6.0 where the exposure increases, making 30% of the zones highly vulnerable. The projected increase in exposure to climatic hazards will worsen the vulnerability of smallholder agricultural systems in future unless the current adaptation deficit is sufficiently addressed. This study maps the temporal dynamics of vulnerability unlike the prevailing snapshot assessments at subnational-level for Ethiopia. The study seeks to assist the decision-making process to build resilience to climate change in Ethiopia and other low-income countries with similar geophysical and socio-economic conditions.